Single‐dose prolonged drug provocation test, without previous skin testing, is safe for diagnosing children with mild non‐immediate reactions to beta‐lactams. Issue 8 (24th March 2021) - Prieto, Ana; Muñoz, Candelaria; Bogas, Gádor; Fernández‐Santamaría, Rubén; Palomares, Francisca; Mayorga, Cristobalina; Salas, Maria; Doña, Inmaculada; Torres, María José
Abstract: Introduction: Mild non‐immediate reactions (NIRs) to beta‐lactams (BLs) are the most frequent manifestation of drug allergy in children. The diagnostic approach is complex as the utility of skin tests (STs) and lymphocyte transformation tests (LTTs) is controversial. Drug provocation test (DPT) is the gold standard, although no standardized protocols exist. We aimed to investigate the utility of DPT in a unique dose without previous STs, and LTTs in the diagnosis of NIRs to BLs in children. Methods: We prospectively evaluated children 0–14 years old referred to the Regional University Hospital of Málaga during 2017–2020 reporting NIRs to BLs. We performed a DPT with a unique dose followed by regular treatment at home. If positive, STs and LTTs were done after the reaction had disappeared. Results: We included 194 children, having 24 (12.4%) a positive DPT. The main culprit was AX (70.1%) followed by AX‐clavulanic acid (CLV) (26.8%) and the main symptoms maculopapular exanthema (MPE) (49.5%) and delayed‐urticaria (48.5%). A decrease ( p  = 0.013) in the interval of days between drug administration and onset of symptoms was observed in positive DPT compared with the original reaction (3.5 vs 6 days), with no differences in the overall percentage of MPE and delayed‐appearing urticaria ( p  = 0.551). No severe reactions occurred during DPT. Moreover, STs were positive in 13.33% and LTTs in 52.9%. Conclusions: Single‐dose DPT without previous STs is a safe and useful way to assess NIRs to BLs in children. LTT has shown to be useful, confirming a T‐cell mechanism involved in these reactions. Abstract : Allergy was confirmed in the 12.4% of children reporting non‐immediate reactions to beta‐lactams. A shorter interval of days of treatment for reaction onset was found in DPT when comparing with the original reaction, but no differences were found regarding the percentage of experienced symptoms. Delayed reading‐intradermal and lymphocyte transformation tests were positive in 13.33% and 52.9% of allergic children, respectively.